The Role of Endogenous Proteins on the Emulsification of Silicone Oils Used in Vitreoretinal Surgery. (21st August 2020) - Nepita, Irene; Repetto, Rodolfo; Pralits, Jan O.; Romano, Mario R.; Ravera, Francesca; Santini, Eva; Liggieri, Libero
Abstract : The present work is aimed at investigating the chemicophysical properties of the interface between silicone oils (SOs) used in vitreoretinal surgery and aqueous solutions, in the presence of surfactant biomolecules. Such molecules are thought to play an important role in the formation of SO emulsions in vitrectomised eyes, in which the natural vitreous body has been replaced with a SO. In particular, we have measured the interfacial tension (IT) and the interfacial dilational viscoelasticity (DV) of the interface between SO (Siluron 1000) and serum proteins (albumin and γ -globulins) at various concentrations in a Dulbecco alkaline buffer. The equilibrium IT value is relevant for the onset of emulsification, and the DV influences the stability of an emulsion, once formed. The study is complemented by preliminary emulsification tests. The experimental results show that, when proteins are dissolved in the aqueous solution, the rheological properties of the interface change. The IT decreases significantly for physiological protein concentrations, and the DV modulus achieves high values, even for small protein concentrations. The emulsification tests confirm that, in the presence of proteins, emulsions are stable on the time scale of months. We conclude that the measured values of IT in the presence of serum proteins are compatible with the promotion of droplet formation, which, in addition, are expected to be stable against coalescence. Adsorption of biomolecules at the interface with the SO is, therefore, likely to play an important role in the generation of an emulsion in eyes subjected to vitrectomy. These findings are relevant to identify strategies to avoid or control the formation of emulsions in eyes.